Menggali Etika Pengacara dalam Alquran - Tarantang, Jepry (IAIN Palangka Raya, 2015)
The advocates are the professions (officium nobile) who act law enforcers. The advocates as law enforcers guaranteed by the regulation no. 18 the year 2003 about the advocates are tied with the ethics. The ethics of Indonesian Advocates the year 2002 becomes the guidance for the advocates in performing their professions.